Oper in Köln: von den Anfängen bis zur Gegenwart - Schwandt, Christoph 1956-2015 (Berlin Dittrich, 2007)
The opera house designed by Wilhelm Riphahn on Cologne's Offenbachplatz was opened in May 1957. Important works of musical theatre were premiered in the architecturally pioneering theatre building: for example, Wolfgang Fortner's " Bluthochzeit" in its opening year and "Die Soldaten" by Bernd Alois Zimmermann in 1965. Great artistic personalities such as the conductors Günter Wand, István Kertész and John Pritchard have characterised the performances of the Cologne Opera ever since. The Mozart cycle staged by Jean-Pierre Ponnelle and Wagner's "Ring des Nibelungen" by Robert Carsen and Patrick Kinmonth gained international acclaim, and to mark the fiftieth anniversary of today's opera house, a comprehensive account of Cologne's opera history from its beginnings in the 17th century to the present day at the start of the 21st century is now being published for the first time. The authors of the individual chapters are Martina Grempler, Dieter Gutknecht, Egbert Hiller, Eberhard Illner, Johannes Jansen, Klaus W. Niemöller, Stefan Rütter, Kerstin Schüssler-Bach, Christoph Schwandt, Michael Struck-Schloen, Thomas Synofzik, Claudia Valder-Knechtges, Grete Wehmeyer, Robertvon Zahn and Christoph Zimmermann. (Translated with DeepL.com)
Includes bibliographical references (p. 609-618) and index.
Keywords: Kölner Oper; Music history; Theater history; Opera; Cologne (Germany)